Meningkatkan Kecerdasan Emosional melalui Layanan Penguasaan Konten pada Siswa - Susilo Susilo (Journal Prakarsa Paedagogia, 2018)
The purpose of this study was to obtain an increase in low emotional intelligence students through mastery of content in class IX.E Gunungwungkal Pati Middle School 2 Semester II Academic Year 2017/20198. The aim to be achieved in this study is to obtain increased emotional intelligence of students through content mastery services in class IX.E Gunungwungkal Pati Middle School 2 Semester II Academic Year 2017 / 2018. Subjects examined in this study were students of class IX.E of SMP Negeri 2 Gunungwungkal Pati Semester II of 2017/1918 Academic Year taken by all children in one class. Research variables: mastery of content (independent variables) and emotional intelligence (dependent variables). Data collection method is the main method of observation, the pendukungg method is interview and documentation. Data analysis uses comparative descriptive. The research was carried out in 2 cycles (cycle I and cycle II) every cycle 3 meeting discussed 3 materials with a time allocation of 40 minutes. Based on the results of research on observations of 7 aspects of improving students 'emotional intelligence, it can be said that through the service of mastering the content of students' emotional intelligence can increase. This is evidenced by what is obtained from every observation made before the action and after the cycle which shows that the emotional intelligence of students has increased, namely in the pre cycle 14.2 in the first cycle: 15, 1 and in the second cycle: 26. Based on the results of the study discussion can It was concluded that content mastery services could improve emotional intelligence of class IX.E students of Gunungwungkal Pati Middle School 2 Semester II Academic Year 2017/2018.